Wastewater treatment of a fruit processing plant pulp - Alcarraz Curi, Mario (2010)
There is a growing concern in environmental pollution levels of the neighboring ecosystems fruit processing plant by the discharge of untreated industrial effl uents and proper control of the authorities, because many of them have not considered the management their effl uents into the design of the plant. The objective of this research is to characterize and manage the processing effl uent. We conclude that the processing effl uents have a high potential for contamination by the abundant organic load and that have achieved the primary treatment of this potential reduction to acceptable limits by Peruvian law (98.1% turbidity removal and reduction of BOD Oxygen 96.58%), allowing the reduction of water consumption, release of hardship and its incorporation as a business friendly environment for approval of environmental authorities and the community as a whole.